2016
DOI: 10.1021/acsnano.6b00258
|View full text |Cite
|
Sign up to set email alerts
|

Facet Control of Gold Nanorods

Abstract: While great success has been achieved in fine-tuning the aspect ratios and thereby the plasmon resonances of cylindrical Au nanorods, facet control with atomic level precision on the highly curved nanorod surfaces has long been a significantly more challenging task. The intrinsic structural complexity and lack of precise facet control of the nanorod surfaces remain the major obstacles for the atomic-level elucidation of the structure-property relationships that underpin the intriguing catalytic performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 105 publications
(275 reference statements)
5
102
0
Order By: Relevance
“…The gradually formed Au ions may act as structure-directing foreign ions that preferentially adsorb onto the different BiVO 4 surfaces to engineer high-index surfaces via thermodynamic control, kinetic control, and selective chemical etching. [30] A similar Au ionguided formation of truncated octahedral and cuboctahedral Cu 2 O has been reported. [31] Interestingly, the direct addition of the same amount of AuCl 4 − into the reaction system leads to According to Steno's law, the Miller indices of the exposed polyhedra facets can be assigned according to the angles between corresponding facets because the angles are always constant.…”
Section: Polyhedral 30-faceted Bivo 4 Microcrystals Predominantly Encsupporting
confidence: 62%
“…The gradually formed Au ions may act as structure-directing foreign ions that preferentially adsorb onto the different BiVO 4 surfaces to engineer high-index surfaces via thermodynamic control, kinetic control, and selective chemical etching. [30] A similar Au ionguided formation of truncated octahedral and cuboctahedral Cu 2 O has been reported. [31] Interestingly, the direct addition of the same amount of AuCl 4 − into the reaction system leads to According to Steno's law, the Miller indices of the exposed polyhedra facets can be assigned according to the angles between corresponding facets because the angles are always constant.…”
Section: Polyhedral 30-faceted Bivo 4 Microcrystals Predominantly Encsupporting
confidence: 62%
“…In the absence of Ag + ions, the Au NRs transformed into elongated trisoctahedral nanoparticles (ETOH NPs) ( Figure 1B), which is in line with our previous observations. 69 Overgrowth of quasi-spherical Au nanoparticles under similar conditions resulted in the formation of high-index faceting nanotrisoctahedrons each of which was enclosed by 24 {221} facets. 34 In the presence of Ag + ions, strikingly different geometric transformations were observed upon NR overgrowth.…”
Section: Resultsmentioning
confidence: 99%
“…60 Recently, we further demonstrated that more rigorous control of Au NR facets with atomic level precision could be achieved using cuprous (Cu + ) foreign ions and halide-containing surfactants as unique pairs of surface capping competitors to maneuver the facet evolution during NR overgrowth. [68][69] In comparison to Cu + ions, Ag + ions have been more widely used in combination with various surfactants to guide the morphology-controlled overgrowth of Au NRs. A large variety of NR-derived anisotropic geometries, such as nanodumbbells, starfruit-shaped NRs, dogbone-like NRs, concave nanocuboids, and arrow-headed NRs, have been obtained through Ag + -and CTAB-coguided NR overgrowth processes.…”
Section: Introductionmentioning
confidence: 99%
“…9,22,23 Moreover, precise facet control is vital to the optimization of the catalytic performance of GNRs. Quantitative assignment of the crystallographic facets exposed on the surfaces of GNRs, however, has long been a subject under intense debate.…”
Section: -21mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] GNRs exhibit intense longitudinal surface plasmon resonance (LSPR), whose wavelength is controlled by the ratio of the length to the width of the GNRs (the aspect ratio, AR), as well as a weaker transverse surface plasmon resonance (TSPR) that is located at $520 nm. [2][3][4][5][6][7][8][9] The LSPR is tuned towards longer wavelengths and into the near-infrared spectrum as the AR increases. To date, a number of successful methods, such as electrochemical, 1 photochemical, 10,11 seed-mediated, 12 and template methods, 13 have been developed to synthesize GNRs.…”
Section: Introductionmentioning
confidence: 99%